Atores virtuais autônomos para sistemas narrativos interativos - Samir Araujo de Souza (2009)
Interactive Storytelling (IS) is a multidisciplinary research area that has attracted a large number of researchers in recent years. There are two main research lines within the major area: emergent and non emergent stories. However, there are few works exploring the perspective of creating IS systems that conduct emergent stories using autonomous intelligent agents as virtual actors. In this paper we propose a model of a synthetic mind for virtual actors that will make them interpret a role of a given character contextualized by a complete story. We discuss the model architecture, implement a prototype, and present some proof-of-concept experiments to show its effectiveness.